Impact of work-life balance on employee performance: a case of ACI Godrej Agrovet Private Limited - Prottasha, Tamrina Bintay Rahman (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.